The Analysis Of The Students’ Difficulty in Memorizing English Vocabulary in Elementary School - Mailasari, Dewi Ulya (Journal of English Teaching and Learning Issues, 2018)
This article describes the students’ difficulty in memorizing English vocabulary in Integrated Islamic Elementary School (SDIT) Amal Insani Jepara.  This study uses a descriptive qualitative method. The result denotes that students have difficulties in memorizing vocabulary including there is no visible intrinsic motivation from students, considering English as just another compulsory subject. In addition to the factors of integration and talent, it seems that attitudinal and motivational factors take the main role of the difficulties of students of SDIT Amal Insani in remembering English vocabulary. Students with a high level of intelligence coupled with high enthusiasm, because there is a reward from the teacher, easy to remember vocabulary as well as remembering other subject matter. Students with a priori and low motivation attitude find it difficult to remember the vocabulary that has been given.